محاولة تطبيق نظام الإنتاج في الوقت المحدد (JIT) في المؤسسات الصناعية الجزائرية دراسة ميدانية للشركة الجزائرية الإلكترونيك (Condor) ببرج بوعريريج - بن عامر, صافية; برحومة, عبد الحميد (Recherches économiques et managériales; Vol. 12 No 01 (2018): RECHERCHES ÉCONOMIQUES ET MANAGÉRIALES(Décembre), 2020)
هدفت الدراسة إلى معرفة مدى إمكانية نجاح تطبيق نظام الإنتاج في الوقت المحدد(JIT) في المؤسسات الصناعية الجزائرية، حيث يعد أسلوب إداري حديث يقوم على أساس استخدام الموارد الصحيحة لإنتاج الكميات المحدد والمطلوبة في الوقت المحدد وبأقل تكلفة وبأعلى جودة ممكنة، وتحقيق استجابة لأكبر عدد من العملاء، وبمستوى مخزون منخفض.    وتم التوصل من خلال هذه الدراسة إلى أن إمكانية نجاح تطبيق هذا النظام بالشركة الجزائرية الإلكترونيك (Condor) ممكنة لتوفر الآليات والميكانيزمات الضرورية لذلك، وسينتج عن ذلك تخفيض في التكلفة وتحسين جودة المنتجات، مع تحقيق مستوى عال من الرضا لدى للعملاء، وكذا دعم وتعزيز الميزة التنافسية للشركة. الكلمات الافتتاحية : نظام الإنتاج في الوقت المحدد، رضا الزبون، التحسين المستمر للجودة، الميزة التنافسية. Abstract      The aim of the study is to determine the feasibility of implementing JIT in the Algerian Industrial Enterprises.                 JIT is a modern administrative method based on the use of the right resources to produce the specified quantities required on time, at the lowest possible cost and with the highest possible quality, and responds to the largest number of customers with low level of inventory.      The study concluded that the possibility of successful implementation of this system in the Algerian company Condor is possible due to the availability of suitable tools and mechanisms for this process. This will result in cost reduction and improvement in the quality of products, achieving a high level of customer satisfaction, as well as enhancing competitive advantage of the company. Keywords: Just in time production system, customer satisfaction, continuous improvement of quality, competitive advantage.